DEATH - THE ANSWER TO THE QUESTIONSOR UNANSWERED QUESTION - Markova, Ilinida (E-Journal VFU, 2024)
The only contemplation that can claim eternity, at least as long as the human species exists, is that of death and immortality, seen always in unity, as mutually determined. Moreover, such a unity necessarily foregrounds the sense of man's saying goodbye to his present, and of this act being his most enduring presence in existence - it is the misunderstanding of this potentiality that presupposes the triviality of all available suffering.
Keywords: death; immortality; eternity; suffering; fear